The Gangster and the Bride: The Media Representation of Masculinity and Femininity in News Coverage of Jihadi Terrorists - Krona, Michael (Terrorism and political violence, 2024)
When European nationals left to join Islamic State, the media extensively reported on many of these individuals. Women’s news coverage had a recurrent narrative—the “jihadi bride.” Academic research has strived to analyse the nature of this coverage, effectively critiquing the narrative. Male jihadists have received limited attention in research on the roles of gender and media. This article seeks to contribute to a gap in knowledge concerning the comparative aspects of gendered representations by evaluating the differences between male and female news media coverage of two high-profile cases: the British woman Shamima Begum and the German man Denis Cuspert. Key findings show that Begum is primarily framed as a reject of British society and a “doubly deviant” woman. Cuspert is portrayed as radical, charismatic, active, and influential over youth. While aligning with previous research on gendered media tropes, this study advances knowledge by demonstrating how each individual’s framing does not merely emphasise gendered personality traits but also connects to broader societal and political factors in domestic contemporary cultural settings.